Effect of Ferrule Location on Fracture Resistance of Maxillary Premolars: An In Vitro Study - Sara Koosha; Mahdieh S. Jebelizadeh; Azam S. Mostafavi (International Journal of Dentistry, 2023)
Objectives. The present study aimed to assess the effect of ferrule location on fracture resistance of maxillary premolars. Materials and Methods. A total of 72 extracted human maxillary premolars were selected and randomly assigned to six groups (n = 12 in each) considering ferrule location: circumferential ferrule (CF), without ferrule (WF), buccal ferrule (BF), lingual ferrule (LF), mesial ferrule (MF), and buccal–lingual ferrule (BLF). Cast posts were cemented into the prepared post spaces. Following conventional impression, Ni–Cr crowns were cemented to the specimens. After thermocycling (5,000 cycles, 5–55°C), the specimens were loaded at 45° in a universal testing machine until fracture. Data were analyzed with one-way ANOVA, Kolmogorov–Smirnov, and Tamhane tests. Results. The maximum and minimum mean fracture resistance were related to the CF (1,143.84 N) and WF (514.89 N) groups, respectively, (P=0.039). Fracture resistance in the BF (933.67 N) and BLF (874.01 N) groups was significantly higher than in the MF group (617.54 N) (P=0.001). There was no significant difference between the MF, LF (722.89 N), and WF groups in terms of fracture resistance (P>0.05). Conclusion. Teeth with CF showed maximum fracture resistance. The location of the ferrule effects on the fracture resistance of maxillary premolars and also the mode of failure.